2014
DOI: 10.1103/physrevb.89.184422
|View full text |Cite
|
Sign up to set email alerts
|

Interplay of growth mode and thermally induced spin accumulation in epitaxialAl/Co2TiSi/AlandAl/Co2TiGe/Alcontacts

Abstract: The feasibility of thermally driven spin injectors built from half-metallic Heusler alloys inserted between aluminum leads was investigated by means of ab initio calculations of the thermodynamic stability and electronic transport. We have focused on two main issues and found that: (i) the interface between Al and the closely lattice-matched Heusler alloys of type Co2TiZ (Z = Si or Ge) is stable under various growth conditions; and (ii) the conventional and spin-dependent Seebeck coefficients in such heterojun… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
(48 reference statements)
1
24
2
Order By: Relevance
“…Assuming an energy-independent scattering, our theoretical results predict a positive Seebeck coefficient for the bulk Co 2 TiZ materials, 16,20 a finding which is in contrast to the large, negative values reported experimentally, reaching as much as −30 µV/K in Co 2 TiSi/Ge and −50 µV/K in Co 2 TiSn.…”
Section: A Electronic Conductivity In Co2tisi:dcontrasting
confidence: 68%
See 2 more Smart Citations
“…Assuming an energy-independent scattering, our theoretical results predict a positive Seebeck coefficient for the bulk Co 2 TiZ materials, 16,20 a finding which is in contrast to the large, negative values reported experimentally, reaching as much as −30 µV/K in Co 2 TiSi/Ge and −50 µV/K in Co 2 TiSn.…”
Section: A Electronic Conductivity In Co2tisi:dcontrasting
confidence: 68%
“…19 In a previous study, we have proposed a thermal spin injector based on a thin, latticematched barrier layer of either Co 2 TiSi or Co 2 TiGe between metallic leads. 16 Moreover, we could show that, similar to the insulator case, the loss of half-metallicity is localized within few atomic layers in the proximity of the interface. Thus, its role in the filtering of transmission channels notwithstanding, we find the understanding of the bulk transport properties of particular importance for the design of Heusler-based heterostructures.…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…18. If we made, in the absence of better knowledge, the assumption of energy-independent scattering, our theoretical results would predict a positive Seebeck coefficient for the bulk Co 2 TiZ materials [119,122], a finding which is in contrast to the large, negative values reported experimentally, reaching as much as −30µV/K in Co 2 TiSi/Ge and −50µV/K in Co 2 TiSn [119,120]. Calculating the conductivity via the Kubo-Greenwood formula, we are not limited to such an assumption; rather, the scattering properties of the point defects are taken into account within the framework of the CPA.…”
Section: Accepted Manuscriptmentioning
confidence: 95%
“…The calculations have shown that the hybridization of electronic states of Al with those of the Heusler material occurs in particular for the Cotermination, for which the interfacial bond length is shorter than for the TiSi or TiGe termination. Even in very thin films, however, one finds that the halfmetallic gap is recovered in the central layers of the Heusler alloy, already 3 to 4 atomic planes away from the interface [122]. The conductance of Al/Co 2 TiZ/Al heterostructures perpendicular to the planes is governed by the backscattering of carriers from the interfaces between Al and the Heusler alloy.…”
Section: Accepted Manuscriptmentioning
confidence: 99%